Anticonvulsant Medications in Mitochondrial Disease - Mithal, Divakar S (Pediatric neurology briefs, 2017)
Researchers from Vienna, Austria and Sao Paulo, Brazil studied the known effects of anticonvulsant drugs on mitochondria, using a literature search to include only references to epilepsy associated with mitochondrial disease, and a specific anti-convulsant drug (i.e. levetiracetam) with a specific mitochondrial function (i.e. mitochondrial membrane potential)